Anthocyanin supplementation improves anti-oxidative and anti-inflammatory capacity in a dose–response manner in subjects with dyslipidemia - Zhang, Hanyue; Xu, Zhongliang; Zhao, Huiwen; Wang, Xu; Pang, Juan; Li, Qing; Yang, Yan; Ling, Wenhua (Redox biology, 2020)
Anthocyanins, one of the major plant bioactive substances, possess anti-oxidative and anti-inflammatory capacity. However, their dose–response relationship has remained unclear. The present study investigated the dose–response relationship of anthocyanins with oxidative stress and inflammation in subjects with dyslipidemia. and Participants: A total of 169 participants with dyslipidemia were randomly assigned to placebo (n = 43), anthocyanins 40 mg/day (n = 44), 80 mg/day (n = 40), or 320 mg/day (n = 42) groups. Urine 8-iso-prostaglandin F2α (8-iso-PGF2α), 8-hydroxy-2′-deoxyguanosine (8-OHdG) and serum malonaldehyde (MDA), total superoxide dismutase (T-SOD), UA (uric acid), interleukin (IL)-6, IL-10, tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) were measured at baseline, at 6 weeks, and at 12 weeks. Anthocyanin supplementation (320 mg/day) for 6 weeks significantly improved T-SOD versus baseline (P < 0.05). A slight reduction in serum IL-6, TNF-α, and urine 8-iso-PGF2α from the baseline was observed at 12 weeks in the group receiving 40 mg/day anthocyanins. Anthocyanins (80 mg/day) significantly reduced serum IL-6 (−20%), TNF-α (−11%) and urine 8-iso-PGF2α (−27%) versus baseline (P < 0.05). Moreover, 320 mg/day anthocyanin supplementation reduced serum IL-6 (−40%), TNF-α (−21%), MDA (−20%) and urine 8-iso-PGF2α (−37%) and 8-OHdG (−36%) than 80 mg/day and 40 mg/day anthocyanins, P value < 0.05. Anthocyanin supplementation has dose-response relationships with decreased inflammatory cytokines IL-6, TNF-α and oxidative stress biomarkers 8-iso-PGF2α, 8-OHdG and MDA (P for trend, <0.05). Furthermore, a strong positive correlation was observed between the changes in the urine 8-iso-PGF2α , 8-OHdG levels and serum IL-6 levels in subjects from anthocyanin groups after 12 weeks of treatment. Supplementation of anthocyanins for 12 weeks positively improved the anti-oxidative and anti-inflammatory capacity in a dose–response manner in individuals with dyslipidemia. [Display omitted] •Anthocyanins improve oxidative stress in a dose-response manner.•Anthocyanins improve anti-inflammatory capacity in a dose-response manner.•80 mg/day anthocyanin could reach the threshold level for producing beneficial functions after 12-week intervention.•Anthocyanins prevent the progression of metabolic diseases in subjects with dyslipidemia.